Fluorescein Staining of Intraocular Lenses - Gerding, Heinrich (Klinische Monatsblätter für Augenheilkunde, 2018)
Background Recent case reports have indicated that intraocular lenses may be discoloured by systemically or locally applied fluorescein. Since very few data are available on the susceptibility of intraocular lenses to fluorescein, an experimental survey on lens discolouration was performed.Material and Methods Intraocular lenses fabricated from polmethylmethacrylate (PMMA), silicone, hydrophobic acrylic copolymers, and hydrophilic acrylic copolymers were exposed to 10% fluorescein. Staining effects were determined by standardised quantification of light transmission.Results Intraocular lenses fabricated from PMMA, silicone, or hydrophobic acrylic copolymer did not exhibit any measurable dye uptake after exposure to fluorescein. Intensive and rapid discolouration occurred in hydrophilic acrylic intraocular lenses. The transmission of blue light was reduced by 22% after 1 second and by 74% after 10 minutes of dye exposure.Conclusions The results indicate that hydrophilic acrylic intraocular lenses develop rapid and intensive discolouration and reduced light transmission after exposure to fluorescein. Lenses fabricated from other materials (PMMA, silicone, hydrophobic acrylic copolymers) were not discoloured by fluorescein staining.
Keywords: cataract; pharmacology; biochemistry; physiological optics